Expression Profiles of 2 Phosphate Starvation-Inducible Phosphocholine/Phosphoethanolamine Phosphatases, PECP1 and PS2, in Arabidopsis - Angkawijaya, Artik Elisa; Ngo, Anh H.; Nguyen, Van C.; Gunawan, Farrel; Nakamura, Yuki (Frontiers in Plant Science, 2019)
Phosphorus is essential for plant viability. Phosphate-starved plants trigger membrane lipid remodeling to replace membrane phospholipids by non-phosphorus galactolipids presumably to acquire scarce phosphate source. PECP1 and PS2 belong to an emerging class of phosphatase induced by phosphate starvation and dephosphorylates phosphocholine and phosphoethanolamine in vivo. However, detailed spatiotemporal expression pattern as well as subcellular localization has not been investigated yet. Here, by constructing transgenic plants harboring functional translational promoter-reporter fusion system, we showed the expression pattern of PECP1 and PS2 in different tissues and in response to phosphate starvation. Besides, the Venus fluorescent reporter revealed that both are localized at the ER. Characterization of transgenic plants that overexpress PECP1 or PS2 showed that their activity towards phosphoethanolamine may be different in vivo. We suggest that PECP1 and PS2 are ER-localized phosphatases that show similar expression pattern yet have a distinct substrate specificity in vivo.